Determination of Plant Density on Yield of Sorghum Intercropping with Haricot Bean at Fadis and Babile - Umata, Habte Berhanu; Debelo, Adugna Hunduma (ABC Journal of Advanced Research, 2018)
Haricot bean is a principal food crop particularly in Southern and Eastern part of Ethiopia, where it is widely intercropped with maize and sorghum, respectively, to supplement farmer’s income (EPPA, 2004). This experiment was handling the appropriate seeding rate on yield of sorghum and haricot bean grown with intercropping system at Eastern Hararghe areas. This activity was done at two locations, Babile and Fadis in RCBD design. The research result showed that, there was significance difference among treatments. treatment (25cmsorghum*30cmharicotbean) and (30cmsorghum and 30cmharicotbean) have more yield when compared to the other both in terms of yield and land equivalent ratio  .Even though the sole sorghum yield per hectare were relatively looks like high, the cumulative yield of intercropping yield were higher than the sole sorghum. At both location (Fadis and Erer) the data obtained were similar. This indicates that similar recommendation for the two locations.